Mental Health Law in the United Arab Emirates: An Analysis - Ajmal, Ali; Rasool, Faiza (Annals of Human and Social Sciences, 2024)
This research aims to study mental health law in the United Arab Emirates. The UAE enacted Federal Law No. 10 of 2023 on mental health, which is a comprehensive and well-developed legislation in the field of mental health. The doctrinal legal analysis research method was employed to study mental health law in the United Arab Emirates. Mental health law in the UAE guarantees the safeguarding of the rights and dignity of psychiatric patients, along with the provision of health care and the regulations of relations between psychiatric patients and people related to them, including employed and employee relations. To meet the objectives of mental health law in the United Arab Emirates, it is recommended that infrastructure be developed, mental health professionals be specialized trained, and awareness of mental health be spread.